2011
DOI: 10.1007/s00595-009-4305-1
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast carcinoma simulating linitis plastica of the colon: Report of a case

Abstract: A 48-year-old woman developed a mobile abdominal mass in the course of treatment for recurrent breast cancer. Imaging studies indicated linitis plastica of the colon. She underwent surgery because of the stenosis of the transverse colon. An examination of the resected specimen revealed a segmental stricture, thickening of the entire wall, and a granular mucosa resembling cobblestones. Microscopic findings of the colon lesion were very similar to those of her primary, invasive lobular carcinoma of the breast. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…23 patients had metastases to the colon (11%), 16 presenting with obstruction/stenosis, 2 with multiple strictures/diffuse infiltration, 2 with polypoid lesions, 1 with linitis plastica, 1 with asymptomatic abdominal mass, and in 1 case presentations' symptoms were not reported [1, 2, 47, 53, 54, 6172]. …”
Section: Case Reports and Results From The Literaturementioning
confidence: 99%
“…23 patients had metastases to the colon (11%), 16 presenting with obstruction/stenosis, 2 with multiple strictures/diffuse infiltration, 2 with polypoid lesions, 1 with linitis plastica, 1 with asymptomatic abdominal mass, and in 1 case presentations' symptoms were not reported [1, 2, 47, 53, 54, 6172]. …”
Section: Case Reports and Results From The Literaturementioning
confidence: 99%
“…In the case of metastatic BC simulating colon linitis plastica reported by Okido et al, the biopsy showed necrotic tissue and failed to find carcinoma. The postoperative histological findings confirmed the colon metastasis from breast ILC 19. Carcoforo et al documented a 73-year-old women referred with abdominal pain, nausea, and emesis without oncologic history.…”
Section: Discussionmentioning
confidence: 68%
“…The infiltration of metastatic lobular carcinoma was found to be of a diffuse pattern through the bowel wall and a linitus plastica-like thickening within the stomach, whereas invasive ductal metastases were nodular in nature 20. Similarly, in a case report by Okido et al 21, a metastatic lobular breast cancer presented as linitus plastica of the colon. Few case reports have documented metastatic ductal breast carcinoma to the colon22–27 and even rarer to the rectum 28.…”
Section: Discussionmentioning
confidence: 87%